2015
DOI: 10.1002/j.0022-0337.2015.79.12.tb06040.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Local Anesthesia Simulation Model with Dental Students as Novice Clinicians

Abstract: The aim of this study was to evaluate the use of a local anesthesia (LA) simulation model in a facilitated small group setting before dental students administered an inferior alveolar nerve block (IANB) for the irst time. For this pilot study, 60 dental students transitioning from preclinical to clinical education were randomly assigned to either an experimental group (N=30) that participated in a small group session using the simulation model or a control group (N=30). After administering local anesthesia for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 8 publications
2
46
0
Order By: Relevance
“…Despite elevated stress surrounding the simulated event, our students overwhelmingly supported simulation as an educational enterprise. This is probably because training in clinical subjects that incorporates realistic simulations has been found to benefit learners' perceived competence and confidence 23, 37 39 Our positive evaluations are consistent with those in another study investigating learner attitudes towards medical emergency simulation, specifically with regard to self‐confidence, team training, and educational objectives 40 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Despite elevated stress surrounding the simulated event, our students overwhelmingly supported simulation as an educational enterprise. This is probably because training in clinical subjects that incorporates realistic simulations has been found to benefit learners' perceived competence and confidence 23, 37 39 Our positive evaluations are consistent with those in another study investigating learner attitudes towards medical emergency simulation, specifically with regard to self‐confidence, team training, and educational objectives 40 .…”
Section: Discussionsupporting
confidence: 80%
“…Simulation exercises used in dental education vary in complexity and technological requirements and can include modalities such as representative models, 23 virtual patients, 16, 42 standardized patients, 17, 43 and manikins 21 . Consistently, in those studies, similar cohorts at the same dental school participating in simulations utilizing both standardized patients and high‐fidelity manikins reported similar rates of positivity towards the experience.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In different fields of dentistry, g. g. tooth extractions, it has been shown that practical skill training on models can significantly improve the performance of students prior to the transition to real patient [17,18]. Local anesthesia training models are also a valuable didactic complement and have beneficial effects [10,13,14]. Students who have used a preclinical training model for practising local anesthesia considered it a useful preparation for their first injection in a human [14].…”
Section: Discussionmentioning
confidence: 99%
“…They are also mentioned in the International guidelines for first aid and resuscitation as an effective method of teaching [12]. In the field of dental medicine, there are numerous studies that emphasize the importance of innovative learning approaches, also the use of mannequin training models [10,13,14,15]. However, the focus of the training should be on the actual real situation [10].…”
Section: Introductionmentioning
confidence: 99%